2017
DOI: 10.1001/jamainternmed.2017.2842
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Ozone Exposure With Cardiorespiratory Pathophysiologic Mechanisms in Healthy Adults

Abstract: IMPORTANCE Exposure to ozone has been associated with cardiovascular mortality, but the underlying biological mechanisms are not yet understood.OBJECTIVE To examine the association between ozone exposure and cardiopulmonary pathophysiologic mechanisms. DESIGN, SETTING, AND PARTICIPANTSA longitudinal study involving 89 healthy adult participants living on a work campus in Changsha City, China, was conducted from December 1, 2014, to January 31, 2015. This unique quasiexperimental setting allowed for better char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(116 citation statements)
references
References 52 publications
6
106
1
1
Order By: Relevance
“…Based on the same field study, we previously evaluated associations between pollutant exposures and biomarker outcomes. 6 We found significant associations of either 24-hour O 3 exposure or 2-week O 3 exposure with a biomarker of platelet activation (plasma-soluble P-selectin) and systolic blood pressure, suggesting that O 3 exposure may increase cardiovascular disease risk via blood pro-coagulation and blood pressure increases. The aim of this study was to examine the impact of temporarily removing either ESPs alone or both ESPs and HEPA filters from the 3-part (F8-ESP-HEPA) air-handling systems on cardiorespiratory function and biomarkers reflecting cardiorespiratory pathophysiology.…”
Section: Introductionmentioning
confidence: 70%
“…Based on the same field study, we previously evaluated associations between pollutant exposures and biomarker outcomes. 6 We found significant associations of either 24-hour O 3 exposure or 2-week O 3 exposure with a biomarker of platelet activation (plasma-soluble P-selectin) and systolic blood pressure, suggesting that O 3 exposure may increase cardiovascular disease risk via blood pro-coagulation and blood pressure increases. The aim of this study was to examine the impact of temporarily removing either ESPs alone or both ESPs and HEPA filters from the 3-part (F8-ESP-HEPA) air-handling systems on cardiorespiratory function and biomarkers reflecting cardiorespiratory pathophysiology.…”
Section: Introductionmentioning
confidence: 70%
“…105 In another study, short-term ozone exposure was linked to BP. 106 Moreover, 2 previous studies found that ozone exposure was negatively (beneficially) or not associated with BP, 80,107 but a recent study has reported a positive association between ozone and both systolic and diastolic BP measurements at slightly higher exposure concentrations. 108…”
Section: Impact Of Ozonementioning
confidence: 98%
“…It might be argued that indoor ozone exposure, although substantial, occurs at concentrations below a “health threshold.” However, recent studies do not support the presence of a threshold for short‐term mortality nor for adverse cardiorespiratory indicators …”
Section: Discussionmentioning
confidence: 95%
“…However, recent studies do not support the presence of a threshold for shortterm mortality 2,49 nor for adverse cardiorespiratory indicators. 50 When indoors, humans are exposed not only to ozone, but also to products of ozone-initiated chemistry. 20,23,36,[51][52][53][54][55][56][57][58][59][60][61][62][63][64] Some of these products (eg, hydroxyl radicals, hydrogen peroxide, organic peroxides, formaldehyde, dicarbonyls, secondary organic aerosols) potentially contribute to the total mortality associated with long-term exposure to ozone as evaluated using measured or modeled outdoor ozone concentrations.…”
Section: Exposure To Indoor Ozone and Its Oxidation Productsmentioning
confidence: 99%